Napravlenija naucno-issledovatel'skoj raboty laboratorii sportivnoj antropologii, morfologii i genetiki VNIIFKa - Abramova, T. F.; Nikitina, T. M.; Kocetkova, N. I. (Teorija i Praktika fiziceskoj Kul'tury, 2003)
The basic directions of researches in laboratory of sports anthropology of All-Russia scientific research institute of physical culture and sports for all time of its existence are presented. The approaches, criteria and the system morphogenetical estimations of motor potential and the morphological estimation of the current and long-term adaptation of the athlete during training are developed as the result of researches. Results of researches are introduced into the up-to-date practice of Russian athletes training.